Effect of conditioned medium of umbilical cord-derived mesenchymal stem cells as a culture medium for human granulosa cells: An experimental study - Kanadi Sumapraja; Andon Hestiantoro; Isabella Kurnia Liem; Arief Boediono; Teuku Z Jacoeb (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Background: The umbilical cord-derived mesenchymal stem cells conditioned medium (UC-MSCs-CM) produces secretomes with anti-apoptotic properties, and has the potential to prevent apoptosis of granulosa cells (GC) during controlled ovarian hyperstimulation. Objective: To observe the effect of UC-MSCs-CM on the interaction between pro- and anti-apoptotic proteins and the influence of growth differentiation factor 9 (GDF9) production in GC. Materials and Methods: UC-MSCs-CM was collected from umbilical cord stem cell culture on passage 4. GC from 23 women who underwent in vitro fertilization were cultured and exposed to UC-MSCs-CM for 24 hr. Then RNA of the GC was extracted and the mRNA expression of BCL-2 associated X (BAX), survivin and GDF9 were analysed using quantitative real-time PCR. The spent culture media of the GC were collected for measurement of insulin growth factor 1 using ELISA. Results: The expression of BAX was significantly different after UC-MSCs-CM exposure (4.09E-7 vs. 3.74E-7, p = 0.02). No significant changes occurred in survivin, BAX/survivin ratio, and GDF9 expression after UC-MSCs-CM exposure (p > 0.05). The IGF-1 level of the CM was significantly higher after the CM was used as a culture medium for GC (2.28 vs. 3.07 ± 1.72, p ≤ 0.001). A significant positive correlation was found between survivin and GDF9 (r = 0.966, p ≤ 0.001). Conclusion: IGF-1 produced by UC-MSCs-CM can work in paracrine fashion through the IGF receptor, which can inhibit BAX and maintain GDF9 production. Moreover, under the influence of UC-MSCs-CM, GC are also capable of producing IGF-1, which can impact GC through autocrine processes.